2022
DOI: 10.5194/tc-2022-134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permafrost saline water and Early to Mid-Holocene permafrost aggradation in Svalbard

Abstract: Abstract. Deglaciation in Svalbard was followed-up by seawater ingression and the deposition of marine (deltaic) sediments in fjord valleys, while elastic rebound resulted in fast land uplift and the exposure of these sediment to the atmosphere, therefore the formation of epigenetic permafrost. This was then followed by the accumulation of aeolian sediments, which froze syngenetically. The permafrost was drilled in the east Adventdalen valley, Svalbard, 3–4 km from the maximum up-valley reach of post-deglaciat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…7). In addition, thermal modeling of permafrost aggradation during the Early to Middle Holocene in marine sediments of a fjord in Svalbard using mean annual air temperature in the −6 to −4°C range showed that permafrost could aggrade tens of meters in a relatively short time period (~200 yr) (Rotem et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). In addition, thermal modeling of permafrost aggradation during the Early to Middle Holocene in marine sediments of a fjord in Svalbard using mean annual air temperature in the −6 to −4°C range showed that permafrost could aggrade tens of meters in a relatively short time period (~200 yr) (Rotem et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…7). In addition, thermal modeling of permafrost aggradation during the Early to Middle Holocene in marine sediments of a fjord in Svalbard using mean annual air temperature in the −6 to −4°C range showed that permafrost could aggrade tens of meters in a relatively short time period (∼200 yr) (Rotem et al, 2022). The development of tabular massive ice in the ESL raised marine-deltaic sediments involves glacial meltwater recharging an aquifer in the poorly consolidated weathered sandstone beneath the Holocene marine sediments.…”
Section: Freezing Of Water With δD-δ 18 O Slope Value Near the Global...mentioning
confidence: 99%